Metaphors as a Deep Text Predicate in Text Production - Lassan, Eleonora (Respectus Philologicus, 2002)
The article aims at the investigation of the text-generation model offered by the author in her book Discourse of Power and Dissident Thinking in the USSR: Cognitive-Rhetorical Analysis (1995) with respect to political texts. In the given case the possibilities of the model, or to be more precise, its capacity to explain the generation of various textual phenomena, are revealed in fictive, publicistic, and song texts. As the author claims, here the basic metaphor operates in the same way as the predicate does in the sentence structure. It is regarded as the second level of text-generation and is structured above the first level, i. e. the opposition of ideas-frames prevailing in the consciousness of the text creator. As in the case of phonology, the frame opposition may demonstrate the privative, gradual, and equipollent character. According to the type of opposition, the metaphor as a deep predicate multifariously contributes to the assertion of authoritative values.
Keywords: model of text production; levels of text production; textsprimitive; frames; opposition (private, gradual, equipollent); case - grammar; actant frame of the predicate